Long‐Term Effects of an Extensive Cognitive Training on Personality Development. Issue 4 (22nd April 2016) - Sander, Julia; Schmiedek, Florian; Brose, Annette; Wagner, Gert G.; Specht, Jule
Abstract: Previous research found that cognitive training increases the Big Five personality trait Openness to Experience during and some weeks after the intervention. The present study investigated whether long‐term changes happen in Openness to Experience and other personality traits after an extensive cognitive training of memory and perceptual speed. The intervention group consisted of 204 adults (20–31 years and 65–80 years; 50% female) who received daily 1‐hour cognitive training sessions for about 100 days. The control group consisted of 86 adults (21–29 years and 65–82 years; 51% female) who received no cognitive training. All participants answered the NEO Five‐Factor Inventory before and 2 years after the cognitive training. Latent change models were applied that controlled for age group (young vs. old) and gender. In the long run, the cognitive training did not affect changes in any facet of Openness to Experience. This was true for young and old participants as well as for men and women. Instead, the cognitive training lowered the general increase of Conscientiousness. Even an extensive cognitive training on memory and perceptual speed does not serve as a sufficient intervention for enduring changes in Openness to Experiences or one of its facets.